2007
DOI: 10.1104/pp.107.105924
|View full text |Cite
|
Sign up to set email alerts
|

A BELL1-Like Gene of Potato Is Light Activated and Wound Inducible

Abstract: BELL1-like transcription factors interact with their protein partners from the KNOTTED1 family to bind to target genes and regulate numerous developmental and metabolic processes. In potato (Solanum tuberosum), the BELL1 transcription factor StBEL5 and its protein partner POTH1 regulate tuber formation by affecting hormone levels. Overexpression of StBEL5 in transgenic lines produces plants that consistently exhibit enhanced tuber formation, and the mRNA of this gene moves through phloem cells in a long-distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 65 publications
(76 reference statements)
4
34
0
1
Order By: Relevance
“…Based on the wound-induction pattern previously described (Chatterjee et al 2007) and verified in the current study, it is plausible that BEL5-like genes function as a phloem defense signal responsive to mechanical or insect damage. A BEL1-like gene from rice, OsBIHD1, was identified that functions in disease resistance and pathogen defense (Luo et al 2005).…”
Section: What Is the Function Of Bel5 Rnas In The Phloem Of Nontuber-supporting
confidence: 80%
See 2 more Smart Citations
“…Based on the wound-induction pattern previously described (Chatterjee et al 2007) and verified in the current study, it is plausible that BEL5-like genes function as a phloem defense signal responsive to mechanical or insect damage. A BEL1-like gene from rice, OsBIHD1, was identified that functions in disease resistance and pathogen defense (Luo et al 2005).…”
Section: What Is the Function Of Bel5 Rnas In The Phloem Of Nontuber-supporting
confidence: 80%
“…The lower section of midveins contains, in order, starting from the lamina, xylem, phloem, and collenchyma tissue (Esau 1977). Consistent with these results, in potato, the foliar midveins are the primary source of StBEL5 promoter activity (Chatterjee et al 2007). …”
Section: Can Other Mrnas Be Detected In Phloem-enriched Sap?supporting
confidence: 54%
See 1 more Smart Citation
“…As discussed earlier, StBEL5 autoregulates its own gene in stolon tips, where promoter activity is induced by SD (Chatterjee et al, 2007;Lin et al, 2013). Deletion of one of the TTGAC motifs present in the StBEL5 upstream sequence essentially eliminated its promoter activity in stolons and new tubers (Lin et al, 2013).…”
Section: Transcriptional Targets Of Stbel5mentioning
confidence: 99%
“…2). This autoregulation was verified through site mutagenesis in an upstream sequence of the StBEL5 gene (Lin et al, 2013) and helps to explain the SD-induced activity of the StBEL5 promoter in stolons growing in the dark (Chatterjee et al, 2007).…”
Section: Stbel5 a Mobile Signal Controlling Development In Potatomentioning
confidence: 99%